Solid-state structure and condensation reaction of (triphenylmethyl)silanetriol - Kim, JH; Han, JS; Lee, ME; Moon, DH; Lah, MS; Yoo, BR (ELSEVIER SCIENCE SA, 2005)
(Triphenylmethyl)silanetriol [1, (Ph3C)Si(OH)(3)] was obtained in 98% yield by the hydrolysis of (triphenylmethyl)trichlorosilane with ice-water in diethyl ether. Single crystal of [1 (.) acetone] for X-ray crystallographic determination was grown from a saturated acetone solution. In the single crystal X-ray structure analysis, the silanetriol 1 crystallizes in the centrosymmetric triclinic space group with two independent molecules in the asymmetric unit. Two independent molecules of the silanetriols 1 interact with each other and with acetones by intermolecular hydrogen bondings. Such hydrogen-bonding interactions lead to a one-dimensional columnar polymeric tube. Finally, this tube interacts with others to make sheets alternating hydrophobic organic part and hydrophilic hydroxy groups of the molecules 1 and the oxygen of acetones arranged regularly. The silanetriol 1 is very stable compound in solution and in solid states at room temperature, but decomposed in the presence of KOH, and undergoes a condensation reaction with dicyclohexylcarbodiimide (DCC) as strong dehydrating agent to give polysiloxane. The silanetriol 1 reacts with trimethylchlorosilane to give three type siloxane products (Ph3C)Si(OH)(3-n)(OSiMe3)(n) (n = 1, 2, 3). The number (n) of silylation of hydroxy groups on the silanetriol 1 increase with increasing the mol ratio of trimethylchlorosilane used. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: RAY CRYSTAL-STRUCTURE; SI-N BONDS; SILANETRIOLS; ORGANOSILANETRIOLS; SILICON; MODEL; METALLASILOXANES; DERIVATIZATION; ALKYLATION; BASICITY